The Relationship between Learning Style and Training Effectiveness Using Communication Technology for General Insurance Agents. - Shahrizal, Badlishah; Abdul Halim, Abd Majid; Munauwar, Mustafa; Mohmad, Yazam Sharif; Mohammed Abdullahi, Umar (2018)
Attaining training effectiveness will be beneficial for General Insurance Agents in performing their daily activities. The training expenditure for General Insurance Agents, which is accounted in the company’s book under the Agency Related Expenses (ARE), applies to all the practitioners in the general insurance agency force with effect from 1st January 2005 where the training hours and related requirements stipulated in the guidelines set by the Central Bank of Malaysia (BNM) must be complied with. The Financial Mediation Bureau (FMB), now known as Ombudsman for Financial Services (OFS), a unit under the Central Bank of Malaysia, had recorded 609 customers complaints in 2015, 660 in 2014 and 742 in 2013 for General Insurance products. This report shows that the people who introduces the insurance products to the public are not well versed with the products thus the knowledge imparted were different from what it is all about. In the insurance industry, the people who plays the role as link between insurance companies and customers are widely known as agents. This research was conducted in two training session where agents were evaluated to find the best way to improve their basic understanding of product knowledge thus connection to the higher-level knowledge is possible. Results indicate that agents are more comfortable, open-minded and less stressful while learning with their peers compares to instructors. The approach using learning style was developed and had resulted a more relax and conducive learning environment and the training effectiveness achieved served as evidence of improved agents’ performance. Keywords: Learning style; Training; Training effectiveness; Human resource management; Communication technology.